Meaning Across Languages: A Contrastive Study of Causative Structures in English and Indonesian - Arriqah Raihani; Elvida Futri Mahara; Putri Zahriah; Miftahul Jannah; Siti Ismahani (Asosiasi Dosen Muda Indonesia, 2026)
This study examines how causative structures encode meaning in English and Indonesian through a qualitative contrastive analysis. It focuses on differences in agentivity, affectedness, and event structure using authentic written texts from both languages. The findings show that English tends to express causation through explicit and segmented constructions that foreground responsibility, while Indonesian often relies on integrated morphological forms that compress cause and effect. These differences lead to shifts in interpretation and challenges for Indonesian learners of English, particularly in academic writing. The study highlights the importance of meaning based contrastive analysis for understanding cross linguistic variation and improving EFL instruction.